Properties of Included Phloem in Teakwood - Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2018)
In some areas of Indonesia, the heartwood of teak tree (Tectona grandis L.f.) contains included phloem, which is categorized as defects. This paper characterized the colour and chemical properties of such abnormal wood. Three selected trees from Perhutani plantation, Randublatung region, were assessed. The heartwood colour properties were measured by CIELAB system. Result showed that the included phloem-containing heartwood (IPHW) was darker (L*), but less red (a*) and yellow (b*) compared to the adjacent normal heartwood (NHW). The lignin and ash contents were not significantly different in the wood radial direction. In contrast, the level of extractive contents were significantly different between sapwood and heartwood. The amount of ethanol-benzene extractive and solubility in 1% NaOH in the IPHW region were significantly higher than that in normal tissues. The analysis of extractive components using gas chromatography-mass spectrometry showed that the deoxylapachol and lapachol was highly marked in the IPWH region. The obtained results suggest that napthaquinone compounds were related to the protection against wood-destroying organisme attack.